(3bhJ GdeJZi Ydi LGeY GdJQePjs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s; (3eSde Hf GdMLGL Hf eSde GdbTjQj GdfjSGHhQqi, CHh GdMSjf,J (B261 (3g` s ((3Ydi Hf eMeO hKGH s)
(3ChdgG (B:s
(3gPG GdcJGH GdQGHY eeG hYOJ HhVYg Ydi GdcJH GdSJI , hgh JYdjb Ydi LGeY CHj YjSi GdJQePi , Ydi feW eG YdbJg Ydi UMjM GdHNGQi GdeSei HGdJhTjM s
(3BNQgG (B:s
(3bGd ai fgGjI GdeQGO HWhHi ai gPG GdMOjK aYdi ef GdWjH , dG GdLfI hGd GdTLQI GdJi ajgG ceG jQGO ai ZjQg ef GdCMGOjK BNQ eG YdbJg Ydi LGeY GdJQePi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3Ydi ghGeTgG JbjjOGJs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs